An application of a model of public management reform to tax administration reform in South Africa - Mkosi, Sakhe Sibabalwe (2019)
Since its statutory creation in 1997, the South African Revenue Service (SARS) has virtually unanimously been seen as a shining light of South African public administration due to its widely perceived efficiency and record of consistently and comfortably surpassing revenue collection targets. Although SARS’ successes have been well documented, little to no research has occurred on the genesis of this institution. In addition, while the field of tax administration is replete with literature from development economists in particular, there does not appear to be much attempt in the archive to study tax administration or tax administration reform from a public administration perspective. This dissertation attempts to do precisely that. It seeks to answer the following linked research questions. Firstly, which forces led to the establishment of SARS? Secondly, with respect to the structural idiosyncrasies which define SARS, which of these elements most significantly distinguish SARS from the rest of the South African public administration and other semi-autonomous revenue authorities and what led to these structural idiosyncrasies? The dissertation does this through a document analysis of various primary and secondary literature such as government publications, statutes, parliamentary publications, commission reports and academic literature. The dissertation perceives the tax administration reform process leading to the creation of SARS through the lens of the sub-field of public administration known as public management reform. In this vein the dissertation applies the Pollitt-Bouckaert model of public management reform as a framework and heuristic device through which the dissertation’s analysis is carried out. These findings are that SARS is most distinguished by its removal from the public service and comparatively high provision for mechanisms of executive control. It further finds that SARS’s aforementioned distinctive features arose from fiscal exigencies, a lack of policy contestation and economic paradigm shifts among key groups of elites. The comparatively high emphasis for executive control is found to be as a result of public service reform priorities in the first post-apartheid government.